Glutamine Synthetase in Spinach Leaves : IMMUNOLOGICAL STUDIES AND IMMUNOCYTOCHEMICAL LOCALIZATION - Hirel, Bertrand (1982)
By polyacrylamide gel electrophoresis, DEAE Sephacel, and hydroxyapatite chromatography, one form of glutamine synthetase has been identified in spinach (Spinacia oleracea L. cv. Monstrueux de Viroflay) leaves. It is localized only inside the chloroplast. The enzyme was purified to homogeneity and specific antibodies against the protein were raised by immunization of rabbits. The intracellular localization of glutamine synthetase in spinach leaves was studied by indirect immunofluorescence microscopy on thin-sectioned spinach leaves. It has been demonstrated that the enzyme is specifically associated with the chloroplasts of parenchymatous cells.